The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1086/520584
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral Budding of Marburg Virus: VP40 Retargets Viral Glycoprotein GP to the Basolateral Surface

Abstract: Virus budding from the basolateral domain of infected polarized cells could be one of the mechanisms underlying the quick systemic infection induced by Marburg virus (MARV). We found that MARV buds from the basolateral pole of hepatocytes and bile epithelial cells in infected guinea pigs, which leads to the release of infectious virus into the vascular system. Basolateral budding might be orchestrated by the basolaterally located MARV matrix protein VP40, which induces a partial relocalization of MARV glycopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 13 publications
2
47
0
Order By: Relevance
“…Late in infection, ongoing cell-to-cell fusion and virus replication cause extensive cytopathic effects and likely disrupt all basolateral trafficking pathways. The consecutive accumulation of the glycoproteins at apical surfaces might be triggered by an apical G/F retargeting promoted by the M protein, as proposed previously for other viruses (25,29,30,34,68,69). However, there is no evidence so far that G, F, and M meet and interact intracellularly before reaching the plasma membrane.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Late in infection, ongoing cell-to-cell fusion and virus replication cause extensive cytopathic effects and likely disrupt all basolateral trafficking pathways. The consecutive accumulation of the glycoproteins at apical surfaces might be triggered by an apical G/F retargeting promoted by the M protein, as proposed previously for other viruses (25,29,30,34,68,69). However, there is no evidence so far that G, F, and M meet and interact intracellularly before reaching the plasma membrane.…”
Section: Discussionmentioning
confidence: 60%
“…Envelope proteins can even be expressed at opposing membranes. Here, partial retargeting of the glycoproteins by the matrix protein to the site of budding is believed to be required for virus release (25,29,30,34,68,69). Resembling measles virus (29), NiV M, F, and G proteins possess opposing targeting signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, analyses using influenza virus, VSV, and human respiratory syncytial virus showed that while their glycoproteins are located at the site of virus budding, they are not the direction-determining factors (6,50,74). For Marburg virus and measles virus, the matrix protein was described to be the determining factor for directional virus release (33,51).…”
Section: Discussionmentioning
confidence: 97%
“…The accumulation of VP40 was observed upon its ectopic expression in filamentous plasma membrane protrusions; the fission of these protrusions results in the release of filamentous virus-like particles (VLPs) into the supernatant (12,13). The coexpression of VP40 with NP or with the viral surface protein GP induces the redistribution of NP and GP to the VP40-enriched plasma membrane protrusions and their subsequent incorporation into released VLPs (14)(15)(16)(17). Based on these observations, it is currently thought that VP40 functions as the main driver of MARV particle assembly and release.…”
Section: Importancementioning
confidence: 99%